2018
DOI: 10.1007/s00115-018-0523-3
|View full text |Cite
|
Sign up to set email alerts
|

Operative Versorgung degenerativer Erkrankungen der Lendenwirbelsäule

Abstract: The treatment of specific lower back pain due to degenerative lumbar pathologies represents an interdisciplinary challenge, requiring both conservative and surgical treatment strategies in a synergistic treatment concept in order to achieve the best results for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Lumbar degenerative diseases, including lumbar degenerative spondylolisthesis, lumbar spinal stenosis, and degenerative scoliosis, involve the pathophysiological process of the natural aging and degeneration of the lumbar intervertebral disc and the paravertebral tissue ( 1 ). These diseases are the main cause of low back pain and leg pain in middle-aged and elderly people and can cause nerve injury in severe cases ( 2 ). With the aging of the global population, the incidence of lumbar degenerative diseases has been gradually increasing ( 3 ), placing a heavy burden on families and society.…”
Section: Introductionmentioning
confidence: 99%
“…Lumbar degenerative diseases, including lumbar degenerative spondylolisthesis, lumbar spinal stenosis, and degenerative scoliosis, involve the pathophysiological process of the natural aging and degeneration of the lumbar intervertebral disc and the paravertebral tissue ( 1 ). These diseases are the main cause of low back pain and leg pain in middle-aged and elderly people and can cause nerve injury in severe cases ( 2 ). With the aging of the global population, the incidence of lumbar degenerative diseases has been gradually increasing ( 3 ), placing a heavy burden on families and society.…”
Section: Introductionmentioning
confidence: 99%
“…Back pain resulting from degenerative changes of the spine represents one of the most prevalent medical conditions in the human population ( Heliovaara et al, 1989 ; Schmidt et al, 2007 ; Raspe, 2012 ). In addition to conservative therapeutic approaches, surgical intervention plays a crucial role in the management of specific back pain associated with structural skeletal abnormalities ( Czabanka et al, 2018 ). Among these structural abnormalities, degenerative spondylolisthesis (DS) frequently affects the lumbar spine of elderly patients ( Pietrantonio et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that the incidence of low back pain increases with age up to 60 years and decreases after that [ 1 ]. Lumbar disc herniation, lumbar spinal stenosis, spondylolisthesis, and other lumbar degenerative diseases are the main causes of low back pain [ 2 ]. Chronic low back pain caused by lumbar degenerative diseases severely affects the daily life of patients and even causes a huge economic burden on society and individuals.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have shown that only approximately half of the patients undergoing conservative treatment have significant improvement in the symptoms of low back pain in the short term, while surgical treatment can not only relieve pain in a short time but also control pain symptoms well within 4 years after surgery [ 4 ]. Chen et al found that surgical treatment has advantages in terms of short-term pain and quality of life compared with conservative treatment [ 5 ], and other scholars believe that early surgical treatment of symptomatic lumbar degenerative diseases is conducive to faster recovery of neurological function [ 2 ]. Traditional surgical approaches include posterior lumbar interbody fusion (PLIF) and transforaminal lumbar interbody fusion (TLIF).…”
Section: Introductionmentioning
confidence: 99%